A new Antillean moth of the genus Enigmogramma Lafontaine & Poole (Noctuidae, Plusiinae) - Becker,Vitor O. (2001)
Enigmogramma antillea sp. n., from Puerto Rico and Cuba, is the second endemic Plusiinae recorded for the Antilles.